2024
DOI: 10.3390/toxics12010092
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Vulnerability to Airborne Nanopollutants

Cristina Hermosillo-Abundis,
Aracely Angulo-Molina,
Miguel A. Méndez-Rojas

Abstract: The toxicological impact of airborne polluting ultrafine particles (UFPs, also classified as nanoparticles with average sizes of less than 100 nm) is an emerging area of research pursuing a better understanding of the health hazards they pose to humans and other organisms. Hemolytic activity is a toxicity parameter that can be assessed quickly and easily to establish part of a nanoparticle’s behavior once it reaches our circulatory system. However, it is exceedingly difficult to determine to what extent each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that magnetic Fe 3 O 4 nanoparticles may lead to apoptosis of RBCs causing eryptosis and hemolysis in the early and later phases [76]. The acanthocyte development-triggering effects of titanium dioxide, silicon oxide, and iron oxide nanoparticles have also been emphasized by various literature studies [77][78][79]. Even the nanoparticles with the highest percentage of hemolysis at 3.0 mg ml −1 concentration among the samples examined had hemolysis value lower than the acceptable upper limit of 5%, changes in the morphological structure of some erythrocytes were observed under the light microscope (see figure 7).…”
Section: Blood Compatibility Testsmentioning
confidence: 99%
“…It has been reported that magnetic Fe 3 O 4 nanoparticles may lead to apoptosis of RBCs causing eryptosis and hemolysis in the early and later phases [76]. The acanthocyte development-triggering effects of titanium dioxide, silicon oxide, and iron oxide nanoparticles have also been emphasized by various literature studies [77][78][79]. Even the nanoparticles with the highest percentage of hemolysis at 3.0 mg ml −1 concentration among the samples examined had hemolysis value lower than the acceptable upper limit of 5%, changes in the morphological structure of some erythrocytes were observed under the light microscope (see figure 7).…”
Section: Blood Compatibility Testsmentioning
confidence: 99%
“…Shimada et al found that PM 2.5 could enter blood circulation in a short time through the "interstitial permeation pathway" induced by the air-blood barrier. PM 2.5 , which enters into circulation, can interact directly with blood cells and vascular tissues, affecting the quality of blood cells, body tissues, and organs [17][18][19]. In spite of this, the biological plausibility of the adverse health effects of ambient particles remains unclear.…”
Section: Introductionmentioning
confidence: 99%